Evaluation of Adherence to Standard Treatment Guidelines in Typhoid Fever - Seemi Gull , Kaennat Munir ,Syed Muarraf Hussain ,Naziha Inam (Journal of Rawalpindi Medical College, 2013)
Background: To analyze adherence to treatment guidelines in typhoid fever. Methods: In this cross sectional study sixty prescriptions from four cities (thirty from public and thirty from private sector) were enrolled. WHO prescribing indicator form was used as a study tool . Probability sampling was employed by using random sampling technique on prescriptions as data was available in the form of prescriptions. Focused group discussions were generated to modify and finalize the tool. Pilot testing was conducted on 10% of the sample size to validate the reliability of tool. The total sample size was 240. Thirty prescriptions were collected from each health care facility according to the guidelines of WHO. Results: Less than 55% of prescriptions revealed proper adherence to treatment. Irrational prescribing included wrong drug, wrong dose, or drug given for short duration. Amongst private sector better adherence to standard treatment guidelines (86%) was seen . Conclusion: It is required to design standard treatment guidelines for typhoid fever